Comércio e serviços mercantis no Brasil: Uma análise de sua evoluç\~ao recente - Luis Claudio Kubota; Marcio Wohlers de Almeida (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– The growing share of the services sector is observed not only in developed countries, but also in many developing economies. In Brazil, services correspond to more than 66% of the valued added in the economy. It is a value close to that observed in richer nations. Notwithstanding, there are few economic studies about the services sector in Brazil, in the current descriptive article tries to bring some new information about the sector. The statistics show that the recent fall in the share of the industry is more pronounced in the European Union than in Brazil. On the other side, the productivity in the services sector is a problem in Brazil, but there are sector which productivity is similar or superior of that observed in the average of the industry. Finally, the statistics show that there is a strong regional inequality in the distribution of services in Brazil.
Keywords: L8; 330; Dienstleistungssektor; Brasilien